Promises and pitfalls of a Pannexin1 transgenic mouse line. - Regina eHanstein; Hiromitsu eNegoro; Naman K. Patel; Anne eCharollais; Paolo eMeda; David C. Spray; Sylvia O. Suadicani; Eliana eScemes (Frontiers Media S.A., 2013)
Gene targeting strategies have become a powerful technology for elucidating mammalian gene function. The recently generated knockout (KO)-first strategy produces a knockout at the RNA processing level and also allows for the generation of conditional KO alleles by combining FLP/FRT and Cre/loxP systems, thereby providing high flexibility in gene manipulation. However, this multipurpose KO-first cassette might produce hypomorphic rather than complete knockouts if the RNA processing module is bypassed. Moreover, the generation of a conditional phenotype is also dependent on specific activity of Cre recombinase. Here, we report the use of an efficient molecular biological approach to test pannexin1 (Panx1) mRNA expression in global and conditional Panx1 KO mice derived from the KO-first mouse line, Panx1tm1a(KOMP)Wtsi. Using qRT-PCR, we demonstrate that tissues from wild-type mice show a range of Panx1 mRNA expression levels, with highest expression in trigeminal ganglia, bladder and spleen. Unexpectedly, we found that in mice homozygous for the KO-first allele, Panx1 mRNA expression is not abolished but reduced by 70% compared to that of wild-type tissues. Thus, Panx1 KO-first mice present a hypomorphic phenotype. Crosses of Panx1 KO-first with FLP deleter mice generated Panx1f/f mice. Further crosses of the latter mice with mGFAP-Cre or NFH-Cre mice were used to generate astrocyte- and neuronal-specific Panx1 deletions, respectively. A high incidence of ectopic Cre expression was found in offspring of both types of conditional Panx1 KO mice. Our study demonstrates that Panx1 expression levels in the global and conditional Panx1 KO mice derived from KO-first mouse lines must be carefully characterized to ensure modulation of Panx1 gene expression. The precise quantitation of Panx1 expression and its relation to function is expected to provide a foundation for future efforts aimed at deciphering the role of Panx1 under physiological and pathological conditions.